2012
DOI: 10.4149/bll_2012_043
|View full text |Cite
|
Sign up to set email alerts
|

Small bowel obstruction due to anomalous congenital peritoneal bands – case series in adults

Abstract: Abstract:Background: Congenital bands cause 3 % of all intestinal obstruction and almost always lead to small bowel obstruction. In adults, obstruction due to bands is even rarer. Materials and methods: A multicenter study in Turkey. From January 2000 to December 2010 inclusive -a period of 10 years -all adult patients admitted to the emergency departments with a clinical diagnosis of acute intestinal obstruction due to congenital peritoneal band were included in the study. Surgery was defi ned as emergency. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 12 publications
0
17
1
1
Order By: Relevance
“…Further, these bands had caused obstruction or compression of bowel in 62.5% patients and entrapment of a part of intestine in 37.5% of cases. Bands containing lose connective tissue and blood vessels, causing small bowel obstruction have been reported by Sozen et al [11].…”
Section: Discussionmentioning
confidence: 88%
“…Further, these bands had caused obstruction or compression of bowel in 62.5% patients and entrapment of a part of intestine in 37.5% of cases. Bands containing lose connective tissue and blood vessels, causing small bowel obstruction have been reported by Sozen et al [11].…”
Section: Discussionmentioning
confidence: 88%
“…In that case the patient was diagnosed with the help of CT and successfully treated with a laparoscopic approach. Although laparotomy is often used in the paediatric population, laparoscopic treatment appears safe and has been described in the majority of the adult patients with congenital bands 1 6 7. Recent work has indicated that non-operative management can be appropriate in selected patients with small bowel obstruction with a virgin abdomen which can also be considered but is controversial 8…”
Section: Discussionmentioning
confidence: 99%
“…Congenital band adhesions are a rare cause of small bowel obstruction in adults 1. The proximal jejunum is infrequently affected by congenital bands according to limited published cases,1–3 with the ileum representing the most commonly affected site. Delayed diagnosis of mechanical obstruction can lead to irreversible bowel ischaemia or perforation, and presents a surgical emergency.…”
Section: Introductionmentioning
confidence: 99%
“…There have been few series and some case reports in the literature. Congenital Peritoneal bands cause 3% of all intestinal obstruction and almost always lead to small bowel obstruction [3]. Their occurrence in adults is an extremely rare condition [4].…”
Section: Discussionmentioning
confidence: 99%